CRYSTALLIZATION CONDITIONS OF FUNDAMENTAL PARTICLES FROM MIXED-LAYER ILLITE-SMECTITE OF BENTONITES BASED ON ISOTOPIC DATA (K-AR, RB-SR AND δ18O) - Clauer N.; Liewig N.; Pierret M.-C.; Toulkeridis T. (My University, 2003)
Rb-Sr and oxygen isotope studies, in addition to K-Ar isotopic determinations published previously, are reported on diagenetic and hydrothermal fundamental particles (particle thickness of 0.03 to 0.05 nm and particle ab size of 0.02 -0.05 µm) of the East-Slovak Basin. The combined data set allows us to ascertain the crystallization conditions of the illite material from two bentonite units collected at two basinal sites located ~20 km apart, and characterized by prolonged diagenetic conditions induced by progressive burial. A bentonite rock characterized by a short hydrothermal event from the Zempleni mountains to the SW of the East-Slovak basin is also studied. For the two first sites, the 18O values increase in one case and decrease in the other, when the size of the diagenetic fundamental particles from bentonite samples increases. These variations suggest that temperature increased in one and decreased in the second of the two samples collected in the basin, while the particles were growing. In the case of the hydrothermal bentonite, the 18O values of the different size fractions consisting of fundamental particles remain about constant, suggesting constant temperature and fluid chemistry. The Rb-Sr dates of the fundamental particles of the three bentonite rocks were systematically higher than the corresponding K-Ar ages. The 87Sr/86Sr ratios, which are initially involved in the particle nucleation, appeared higher than that of contemporaneous sea-water. In all cases, the initial 87Sr/86Sr ratio decreases when particle size increases, which implies supply of external Sr into the bentonite units. This external Sr seems to have had an 87Sr/86Sr ratio close or identical to that of the contemporaneous sea water. This means that Sr, probably of sea-water origin, progressively diffused from host shales into the bentonite units, during burial diagenesis. In turn it favors the suggestion made previously about diffusion of K from shales into the bentonite layers during illitization of the smectite from these units.
Keywords: Illite